2011
DOI: 10.1007/s10681-011-0481-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rice blast resistance gene Pi-z in rice germplasm using pathogenicity assays and DNA markers

Abstract: The Pi-z gene in rice confers resistance to a wide range of races of the rice blast fungus, Magnaporthe oryzae. The objective of this study was to characterize Pi-z in 111 rice germplasm accessions using DNA markers and pathogenicity assays. The existence of Pi-z in rice germplasm was detected by using four simple sequence repeat (SSR) markers (RM527, AP4791, AP5659-1, AP5659-5) closely linked to Pi-z, and was verified using pathogenicity assays with an avirulent strain (IE1k) and two virulent races (IB33 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The observed frequency fitted to the single-gene model. RoyChowdhury et al (2012) found Pi-b blast resistance gene in the national small grain collection and mentioned that RM208 marker is tightly linked to Pi-b gene. Tanweer et al (2015) cloned the Pi-b and Pi-kh genes from Malaysian local rice cultivar Pongsu Seribu 2, thus it is confirmed from their research that Pongsu Seribu 2 contain atleast two dominant genes.…”
Section: Discussionmentioning
confidence: 99%
“…The observed frequency fitted to the single-gene model. RoyChowdhury et al (2012) found Pi-b blast resistance gene in the national small grain collection and mentioned that RM208 marker is tightly linked to Pi-b gene. Tanweer et al (2015) cloned the Pi-b and Pi-kh genes from Malaysian local rice cultivar Pongsu Seribu 2, thus it is confirmed from their research that Pongsu Seribu 2 contain atleast two dominant genes.…”
Section: Discussionmentioning
confidence: 99%
“…They identified five QTLs located on chromosomes 6, 7, 9 and 11. Chowdhury et al (2012) evaluated 111 germplasm accessions against rice blast resistance conferring gene Pi-z. Among the available germplasm accessions, 73 were found to carry the said gene.…”
Section: Significance Of Rice Germplasmmentioning
confidence: 99%
“…492 genes have been cloned and used for crop protection [13]. However, the management of rice blast caused by P. oryzae through the use of disease resistant cultivars has become difficult because of the highly variable nature of the pathogen as well as favorable environmental conditions for infection during the crop season.…”
Section: Identification Of Rice Blast Resistance Genes In South Centrmentioning
confidence: 99%